Labile carbon facilitated phosphorus solubilization as regulated by bacterial and fungal communities in Zea mays. (December 2021) - Huang, Yanlan; Dai, Zhongmin; Lin, Jiahui; Li, Daming; Ye, Huicai; Dahlgren, Randy A.; Xu, Jianming
Abstract: Organic carbon (C) is often applied to agricultural soils to increase soil organic matter, however, its mechanistic effects on soil P transformations and availability resulting from stimulation of microbial activities and changes in microbial communities remain uncertain. This study investigated the responses of soil P availability, P fractions and phoD harboring bacterial and fungal communities to two dose rates (5 and 10 mg C g −1 dry soil) of labile C (glucose) in bulk and rhizosphere soils planted with maize in a P-deficient soil (Oxisol). Both doses of glucose significantly increased available P concentrations (over a 47-day period) in soils without maize, and in the bulk and rhizosphere soils of maize, resulting in the promotion of maize growth. Glucose additions altered soil phoD harboring bacterial and fungal community composition and stimulated the growth of keystone P-solubilizing microorganisms, such as Bradyrhizobium and Eupenicillium, in soils with maize. Co-occurrence network analysis showed that glucose enhanced interactions between phoD harboring bacterial taxa relative to that of fungal taxa, whether in individual networks or in combined networks. Our results highlight the importance of labile C in facilitating changes in soil P-solubilizing bacterial and fungal communities of a P-deficient soil. These findings provide crucial information to guide P-cycling management strategies via microbial regulation in agro-ecosystems. Graphical abstract: Image 1 Highlights: Labile C increased soil available P concentration and promoted maize growth. Labile C increased phoD gene abundance and potential ACP and ALP activities. Enhanced available P derived from altered phoD harboring bacterial/fungal communities.